Cell surface engineering of Saccharomyces cerevisiae combined with membrane separation technology for xylitol production from rice straw hydrolysate - Guirimand, Gregory; Sasaki, Kengo; Inokuma, Kentaro; Bamba, Takahiro; Hasunuma, Tomohisa; Kondo, Akihiko (Applied microbiology and biotechnology, 2016)
Xylitol, a value-added polyol deriving from D-xylose, is widely used in both the food and pharmaceutical industries. Despite extensive studies aiming to streamline the production of xylitol, the manufacturing cost of this product remains high while demand is constantly growing worldwide. Biotechnological production of xylitol from lignocellulosic waste may constitute an advantageous and sustainable option to address this issue. However, to date, there have been few reports of biomass conversion to xylitol. In the present study, xylitol was directly produced from rice straw hydrolysate using a recombinant Saccharomyces cerevisiae YPH499 strain expressing cytosolic xylose reductase (XR), along with β-glucosidase (BGL), xylosidase (XYL), and xylanase (XYN) enzymes (co-)displayed on the cell surface; xylitol production by this strain did not require addition of any commercial enzymes. All of these enzymes contributed to the consolidated bioprocessing (CBP) of the lignocellulosic hydrolysate to xylitol to produce 5.8 g/L xylitol with 79.5 % of theoretical yield from xylose contained in the biomass. Furthermore, nanofiltration of the rice straw hydrolysate provided removal of fermentation inhibitors while simultaneously increasing sugar concentrations, facilitating high concentration xylitol production (37.9 g/L) in the CBP. This study is the first report (to our knowledge) of the combination of cell surface engineering approach and membrane separation technology for xylitol production, which could be extended to further industrial applications.